Family Communication Orientation In The Shift Of Urban Wedding Traditions: An Analysis Of Message Accommodation In Intimate Weddings In Medan City - Arif Hamdani Margolang; Suci Ledian Khairina; Al Wafi (CERED Indonesia Institute, 2026)
The shift in wedding concepts from large-scale communal parties to intimate weddings triggers distinct discourse dynamics within urban family communication. This study aims to dissect the intergenerational communication asymmetry between young couples (Millennials/Gen Z) and parents through the lenses of Family Communication Patterns Theory and Communication Accommodation Theory. Using a qualitative approach with a descriptive case study method, primary data were obtained through in-depth interviews with eight wedding organizer practitioners in Medan City during the 2012–2024 operational period. The results show that proposing the intimate wedding concept tests the relationship between conversation orientation and conformity orientation within the family. To bridge cultural tensions and parents' face management needs, young couples and wedding organizers implement message accommodation tactics through convergent linguistic reframing and spatial-temporal structural compromises in a hybrid model. This study formulates the concept of Negotiated Ritual Modernity, wherein modernity does not eliminate collective traditions but rather reconstructs them spatially and temporally through a professional communication mediation process.